2009
DOI: 10.1002/jbt.20295
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium in apoptosis induced by 7β‐hydroxycholesterol and cholesterol‐5β,6β‐epoxide

Abstract: Oxysterols, such as 7beta-hydroxy-cholesterol (7beta-OH) and cholesterol-5beta,6beta-epoxide (beta-epoxide), may have a central role in promoting atherogenesis. This is thought to be predominantly due to their ability to induce apoptosis in cells of the vascular wall and in monocytes/macrophages. Although there has been extensive research regarding the mechanisms through which oxysterols induce apoptosis, much remains to be clarified. Given that experimental evidence has long associated alterations of calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…However, the fact that the effect of oxLDL was mimicked by exogenous S1P and inhibited by an SK inhibitor suggests that S1P plays a major role. In addition, a recent study in U937 macrophages found that increased intracellular Ca 2+ in response to 7 ␤ -hydroxycholesterol was mediated by infl ux of extracellular Ca 2+ and was nonoscillatory ( 57 ). Both of these features are different from our fi ndings with oxLDL-induced Ca 2+ signaling in BMDM.…”
Section: Inhibition Of Phospholipase C or Ryanodine Receptor Does Notcontrasting
confidence: 99%
“…However, the fact that the effect of oxLDL was mimicked by exogenous S1P and inhibited by an SK inhibitor suggests that S1P plays a major role. In addition, a recent study in U937 macrophages found that increased intracellular Ca 2+ in response to 7 ␤ -hydroxycholesterol was mediated by infl ux of extracellular Ca 2+ and was nonoscillatory ( 57 ). Both of these features are different from our fi ndings with oxLDL-induced Ca 2+ signaling in BMDM.…”
Section: Inhibition Of Phospholipase C or Ryanodine Receptor Does Notcontrasting
confidence: 99%
“…Different oxysterols have distinct impacts on membrane lipid packing [20,21] and thereby interfere with the cholesterol-sphingolipid-enriched raft domains with key roles in a number of signal transduction events [22]. In many cases, increases in cytoplasmic (Ca 2þ ) are the earliest responses to oxysterol or oxidized LDL [23,24], followed by inhibition of prosurvival phospoinositide 3-kinase (PI3K)/3-phosphoinositide dependent protein kinase-1(PDK-1)/Akt signaling [25,26], activation of the Ca 2þ dependent phosphatase calcineurin [27], induction of distinct proapoptotic routes involving the Bad, Bim, or Bax proteins [25,[27][28][29] and suppression of the antiapoptotic Bcl-2/Bcl-xL proteins [25,[29][30][31]. Much of the cytotoxicity attributable to oxysterols is due to their ability to induce apoptosis.…”
Section: Key Pointsmentioning
confidence: 99%
“…We therefore investigated the possible relationships between the NGR-peptide-1 lethal effects, Ca 2+ release and ROS production in U937 cells. Firstly, we analyzed the ability of two Ca 2+ chelators (the cell-impermeant compound BAPTA and the cell-permeant compound BAPTA-AM) and nifedipine (known to block L-type Ca 2+ channels in U937 cells [ 50 ]) to modulate NGR-peptide-1-induced cell death (as determined by annexin-V-FITC/PI staining). In absence of NGR-peptide-1, these inhibitors did not alter surface CD13 levels.…”
Section: Resultsmentioning
confidence: 99%